Mirabelle gets up to mischief - Muncaster, Harriet (2020)
Mirabelle's mum is a witch and her dad is a fairy, and Mirabelle is a bit of both. She likes casting spells with her fairy wand and flying around on her witchy broomstick, but most of all, the thing she really, really likes to do, is cause mischief.
Includes some mischievous things to make and do.
Keywords: Magic -- Juvenile fiction; Witches -- Juvenile fiction; Fairies -- Juvenile fiction; Children's stories; Witches; Magic; Fairies; Children's stories; Children's stories; Fantasy fiction; Fiction; Juvenile works; Fantasy fiction